2023
DOI: 10.1039/d3va00015j
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater-based surveillance of COVID-19 and removal of SARS-CoV-2 RNA across a major wastewater treatment plant in San Antonio, Texas

Abstract: Wastewater-based epidemiology (WBE) targeting SARS-CoV-2 RNA detection in municipal wastewater is considered a valuable tool for COVID-19 surveillance in a community. However, the persistence and removal of SARS-CoV-2 in wastewater...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Previous studies have focused on the fate of viruses throughout WWTPs such as SARS‐CoV‐1 (Wang, Li, Guo, et al 2005; Wang, Li, Jin, et al 2005), pepper mild mottle virus (PMMoV), tobacco mosaic virus (TMV) (Tandukar et al, 2020a), Adenovirus (Hata et al, 2013), and so forth. Since the COVID‐19 pandemic, studies have been published on virus removal from various treatment processes, including individual wastewater treatment steps (Al‐Duroobi et al, 2023), advanced treatment (Polanco et al, 2023), and across the entire treatment plant (Arora et al, 2022; Sherchan et al, 2021; Foladori et al, 2022). These studies sometimes observed virus detection even after advanced treatment in the final effluent of wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on the fate of viruses throughout WWTPs such as SARS‐CoV‐1 (Wang, Li, Guo, et al 2005; Wang, Li, Jin, et al 2005), pepper mild mottle virus (PMMoV), tobacco mosaic virus (TMV) (Tandukar et al, 2020a), Adenovirus (Hata et al, 2013), and so forth. Since the COVID‐19 pandemic, studies have been published on virus removal from various treatment processes, including individual wastewater treatment steps (Al‐Duroobi et al, 2023), advanced treatment (Polanco et al, 2023), and across the entire treatment plant (Arora et al, 2022; Sherchan et al, 2021; Foladori et al, 2022). These studies sometimes observed virus detection even after advanced treatment in the final effluent of wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%